Relationship Between Extent of Learning and ICT Module with VARK Compatibility - Sunitha, N.; Sreedevi, P.; Umajyothi, Y. (Indian Journal of Extension Education, 2019)
The present study on the relationship between Extent of Learning and ICT Module with VARK Compatibility was conducted to identify the learning style preferences of adult learners. The size of the sample comprises of 150 respondents which are selected randomly from five adopted villages of KVK, Rudrur, in Nizamabad district. The findings revealed that extent of learning had significant positive relationship with VARK compatibility of ICT module, gender and age at 0.1 level of probability and at 0.5 levels with education and ICT usage, whereas no significant relation was found with occupation. Hence, it was concluded that irrespective of learning styles the learning through ICT modules occurred equally as the module has VARK learning compatibility. Gender, age, education and ICT usage contributes the extent of learning through ICT modules.
Keywords: Learning style; VARK-Visual; Read/write; Kinesthetic; ICT module